2009
DOI: 10.1063/1.3099594
|View full text |Cite
|
Sign up to set email alerts
|

Giant positive magnetoresistance in Co@CoO nanoparticle arrays

Abstract: We report the magnetotransport properties of self-assembled Co@CoO nanoparticle arrays at temperatures below 100 K. Resistance shows thermally activated behavior that can be fitted by. Efros-Shklovskii variable range hopping (=1/2) and simple activation (hard gap, =1) dominate the high and low temperature region, respectively, with a strongly temperature-dependent transition regime in between. A giant positive magnetoresistance of >1,400% is observed at 10K, which decreases with increasing temperature. The p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Interestingly enough TM-RE codoped polycrystalline In 2 O 3 shows giant positive MR values (85% at T = 2 K) at low temperatures but drops down to very small values as the temperature is raised [15]. Similar behavior was also observed in self-assembled Co@CoO nanoparticle arrays at temperature below 100 K [10], in non-magnetic silver chalcogenides [9], perovskite type manganites and inhomogeneous narrow gap semiconductors [11]. On the other hand, remarkable positive MR of ∼59% at 300 K under 80 kOe magnetic field and 105% under 50 kOe at 5 K have been reported in Co 10 C 90 compacts [4].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly enough TM-RE codoped polycrystalline In 2 O 3 shows giant positive MR values (85% at T = 2 K) at low temperatures but drops down to very small values as the temperature is raised [15]. Similar behavior was also observed in self-assembled Co@CoO nanoparticle arrays at temperature below 100 K [10], in non-magnetic silver chalcogenides [9], perovskite type manganites and inhomogeneous narrow gap semiconductors [11]. On the other hand, remarkable positive MR of ∼59% at 300 K under 80 kOe magnetic field and 105% under 50 kOe at 5 K have been reported in Co 10 C 90 compacts [4].…”
Section: Introductionsupporting
confidence: 69%
“…In addition to this, the matrix too has its role in regulating the magnetic and electrical transport behavior. For non-magnetic metals, semimetals and semiconductors, the MR is usually negligible at 300 K at low magnetic fields [8][9][10]. However, narrow gap semiconductors, heavily disordered semiconductors exhibit a linear response to the magnetic field [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…50 Tan et al 25 have reported a similar temperature dependence of resistance in CoFe superlattice crystals that show CB at low temperatures in three-dimensional arrays of NCs and a large high-field magnetoresistance (MR). Hopping-type transport between localized states has also been observed in monodispersive arrays of Co@CoO core@shell NCs (model granular systems exhibiting positive MR) 51 as well as in granular Zn-doped Fe 3 O 4 polycrystalline materials (the latter show giant tunneling-type MR due to spin polarization in Zn x Fe 3-x O 4 grains aided by superexchange interaction between different magnetic domains separated by the insulating phase). 52 In our experimental system, the Efros-Shklovskii VRH well describes the dependence of R on T over the whole temperature range investigated.…”
Section: Resultsmentioning
confidence: 92%
“…Positive MR values reported in granular systems are often related to various factors, such as curving of carrier trajectories in magnetic fields, shrinkage of localized electronic wave functions, and suppression of hopping paths due to Zeeman splitting of the localized states, depending on the particular case of study. 51 In our junctions, below T V , the extra electrons are frozen and localized, which is a first reason accounting for positive MR. Additionally, Zeeman splitting of the localized states contributing to carrier hopping can also contribute to positive MR in nanostructured arrays, leading to suppression of spindependent transport in the presence of external fields. The exchange coupling between different magnetic domains can enhance the Zeeman splitting of the localized states, leading to large positive MR. 51 On decreasing the temperature further to 10 K, a noteworthy increase in positive TMR is observed that drastically rises up to 300% (Figure 4c).…”
Section: Resultsmentioning
confidence: 98%
“…Above that temperature the conductivity followed Efros-Shklovskii law. In paper [22] the observation of "almost" Arrhenius conductivity was reported in the temperature range 20K < T < 30K in the array of metallic Co nanoparticles. This dependence was well described by (1) with α = 1.1.…”
Section: Polaronic Effect In Granular Systemsmentioning
confidence: 99%